2009
DOI: 10.1186/1752-1505-3-6
|View full text |Cite
|
Sign up to set email alerts
|

Trauma, poverty and mental health among Somali and Rwandese refugees living in an African refugee settlement – an epidemiological study

Abstract: BackgroundThe aim of this study was to establish the prevalence of posttraumatic stress disorder (PTSD) and depression among Rwandese and Somali refugees resident in a Ugandan refugee settlement, as a measure of the mental health consequences of armed conflict, as well as to inform a subsequent mental health outreach program. The study population comprised a sample from 14400 (n = 519 Somali and n = 906 Rwandese) refugees resident in Nakivale refugee settlement in South Western Uganda during the year 2003.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
96
3
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(115 citation statements)
references
References 25 publications
10
96
3
6
Order By: Relevance
“…To this end, a sample was chosen from Tazade and Quratoo camps, based on Morgan Table. The findings revealed that depression disorder is so prevalent in these children that 56% of them suffer from different degrees of depression. These results agree with findings of previous studies (Fazel, 2005;Bogic, et al, 2015;Boehnlein, et al, 2004, andOnyut, et al, 2009). After the attack of so called Islamic State of Iraq and Syria group (ISIS) to different Iraqi cities, the number of refugees entering Kurdistan realm was increased.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…To this end, a sample was chosen from Tazade and Quratoo camps, based on Morgan Table. The findings revealed that depression disorder is so prevalent in these children that 56% of them suffer from different degrees of depression. These results agree with findings of previous studies (Fazel, 2005;Bogic, et al, 2015;Boehnlein, et al, 2004, andOnyut, et al, 2009). After the attack of so called Islamic State of Iraq and Syria group (ISIS) to different Iraqi cities, the number of refugees entering Kurdistan realm was increased.…”
Section: Discussionsupporting
confidence: 83%
“…The 12-month prevalence of major depression is reported in 7% of the American people, and the number of female patients is 1.5 to 3 times more than males (Segal, et al, 2002). Although all people are prone to suffer from psychological disorders, it is especially more common in the homeless, jobless, illiterate, violence victims, harassed women, and neglected senior citizens (Onyut et al, 2009). The same pattern can be found in Iraq, but the several decades of war and civil conflicts have increased the depression rate to 4.7%, as one the countries with the highest depression prevalence (Al-Hamzawi, et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The instruments were interpreted from English into Kinyarwanda, an official language of Rwanda, with the help of 5 students of English interpreting at the National University of Rwanda. The interpreters had been trained in the clinical concept and symptom clusters of PTSD using the PSS-I validated in Kinyarwanda [31]. The CAPS interviewers were N.J., S.S., A.M., and 4 other experts who were postgraduate level collaborators from the University of Konstanz or from the nongovernmental organization vivo.…”
Section: Methodsmentioning
confidence: 99%
“…On the cross analysis of the global total scores of the participants on the GHQ 28 with their age groups it was found that the participants below the age of 35 years and above the age of 55 years were having mean scores of more than 20 with the participants above the age of 75 years having the highest mean score of 26 participants on the GHQ 28 with their education level it was found that the participants who were graduates or having an intermediate level of education were having mean scores of 6 and 5 respectively while the participants having education level of matric or below were having mean scores of more than 20 as shown in table 4. On the cross analysis of the global total scores of the participants on the GHQ 28 with their area of origin it was found that the participants belonging to Bajaur Agency were having mean score of more than 20 while the participants belonging to Momand Agency and Malakand division were having mean scores of less than 20 as shown in table 4.…”
Section: Psychiatric Morbiditiesmentioning
confidence: 99%
“…According to a survey in the Indian Kashmir valley, the ongoing conflict in the valley had a huge toll on the psychosocial health of the population with over one third of the participants having symptoms of psychological distress and majority of them being women [25]. According to an epidemiological study, 48% of the Somali and 32% of Rwandese refugees living in a refugee settlement were found to be suffering from PTSD [26]. In another study on the mental health status of the people displaced from Bosnia and Herzegovina due to conflict, mental health challenges were found to be present in more than 41% of those displaced [27].…”
Section: Idps and Psychiatric Morbiditiesmentioning
confidence: 99%